2010
DOI: 10.1007/s00256-010-1076-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tear of the plantaris tendon: ultrasound and MRI appearance

Abstract: We report a retrospective analysis of the ultrasound and magnetic resonance imaging appearance of five patients with isolated plantaris tendon tears. Both imaging techniques allowed detection of the tear, assessment of its severity and of its location. Compared with magnetic resonance imaging, ultrasound resulted in a less expensive and time-consuming evaluation. Isolated plantaris tendon tears can clinically mimic Achilles tendon tears or thrombophlebitis. Unlike these conditions, plantaris tear has a benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…A total of 20 clinical conditions were identified (Table 22 ). Thirty-five diagnostic articles relevant to the accuracy of MSK-DUSI for diagnosing soft-tissue pathology of the ankle/foot were found [ 122 156 ]. No systematic reviews were found.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 20 clinical conditions were identified (Table 22 ). Thirty-five diagnostic articles relevant to the accuracy of MSK-DUSI for diagnosing soft-tissue pathology of the ankle/foot were found [ 122 156 ]. No systematic reviews were found.…”
Section: Resultsmentioning
confidence: 99%
“…Table 23 reports, the 35 included studies reviewed 1713 patients [ 122 156 ]. The mean age was not stated in nine studies [ 133 , 137 139 , 141 , 150 , 153 , 155 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five cases of this injury were described by Bianchi and colleagues, who reported findings on US and MRI. 30…”
Section: Plantaris Injurymentioning
confidence: 99%